Cloning and functional expression of three xylanase genes from Aspergillus fumigatus in Saccharomyces cerevisiae - Borchardt, Jane (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.